2021
DOI: 10.1111/all.14861
|View full text |Cite
|
Sign up to set email alerts
|

Allergens and their associated small molecule ligands—their dual role in sensitization

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 193 publications
(496 reference statements)
1
48
0
2
Order By: Relevance
“…In fact, the nsLTP fold enables the formation of a hydrophobic tunnel-like cavity where hydrophobic ligands with different sizes can be accommodated (31,37). Similar to nsLTP, a GRP structure is predicted to form a cavity (12) where a ligand, such as biological lipids/membranes, can be bound (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the nsLTP fold enables the formation of a hydrophobic tunnel-like cavity where hydrophobic ligands with different sizes can be accommodated (31,37). Similar to nsLTP, a GRP structure is predicted to form a cavity (12) where a ligand, such as biological lipids/membranes, can be bound (1).…”
Section: Discussionmentioning
confidence: 99%
“…nsLTP was described as the most frequent sensitizer in the Italian subjects with food-dependent exercise-induced anaphylaxis (FDEAIA) ( 35 ). It was reported that the allergenicity of nsLTP, as well as that of other allergens with the function of hydrophobic molecule carrier, could be influenced by the bound ligand which may act as an adjuvant and drives the immune system toward a type 2 (pro-allergenic) response ( 36 , 37 ). For instance, the interaction of Pru p 3 with selected fatty acids was described to increase its IgE binding capacity, whereas the binding of some other lipids did not have the same effect ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some exceptions have been reported, as is the case of wheat LTP, whose ligand binding properties enhanced its conformational flexibility resulting in increased susceptibility to gastroduodenal proteolysis (Abdullah et al, 2016 ). Moreover, ligand‐binding allergens expose the immune system to a variety of biologically active small molecules that could play important and still not well‐understood roles in the sensitisation process in addition to the allergenic protein itself (Chruszcz et al, 2021 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Notably, the majority of studies for the time being has employed allergen extracts which are known to contain LPS and other contaminating material (220)(221)(222). In case of mite Der p 2, a non-lipocalin allergen, the proposed [and debated (223,224)] allergenic mechanism is though interesting because the allergen exhibits structural homology with MD-2, a LPS-binding component of the TLR4 signaling complex (221). Thereby, it was found to facilitate signaling through direct interactions with the complex (221).…”
Section: Receptors Of Innate Immunity Recognizing Lipocalin Allergensmentioning
confidence: 99%